Effect of intravenous adrenaline on electrocardiogram, blood pressure, and serum potassium. Issue 1 (January 1983) - Struthers, A D; Reid, J L; Whitesmith, R; Rodger, J C
Abstract : Increased catecholamines after myocardial infarction may contribute to the development of arrhythmias. We have infused adrenaline intravenously in nine normal volunteers to levels similar to those seen after myocardial infarction. Adrenaline caused an increase in systolic blood pressure, a decrease in diastolic blood pressure, and an increase in heart rate. Adrenaline also produced a decrease in T wave amplitude and an increase in the QTc interval. The serum potassium fell dramatically during the adrenaline infusion from a control value of 4.06 mmol/l to 3.22 mmol/l. Hypokalaemia after myocardial infarction is associated with an increased incidence of ventricular arrhythmias. Thus, circulating adrenaline may increase the frequency of arrhythmias both directly via changes in ventricular repolarisation and indirectly via adrenaline induced hypokalaemia.